2009
DOI: 10.18352/bmgn-lchr.102
|View full text |Cite
|
Sign up to set email alerts
|

Tenure, tourism and timber in Quintana Roo, Mexico: Land tenure changes in forest Ejidos after agrarian reforms

Abstract: We present and apply an analytical framework for understanding land tenure change in the wake of radical land policy modifications in Mexico's communal tenure system. We posit that the changes in land tenure vary as a result of a complex interplay of drivers external and internal to the land tenure unit. Using interview and socio-economic data, we apply this framework to six ejidos in Quintana Roo, Mexico in order to understand the extent to which these ejidos have shifted towards private individual property a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…NAFTA in turn facilitated market penetration into the Mexican countryside, already underway due to urban population growth. However, contrary to expectations of the ETLR and many observers, privatization of ejido lands has not (as yet) occurred (Barnes 2009;Barsamintov et al 2010).…”
Section: Common Pool Resources (Cprs)mentioning
confidence: 67%
“…NAFTA in turn facilitated market penetration into the Mexican countryside, already underway due to urban population growth. However, contrary to expectations of the ETLR and many observers, privatization of ejido lands has not (as yet) occurred (Barnes 2009;Barsamintov et al 2010).…”
Section: Common Pool Resources (Cprs)mentioning
confidence: 67%
“…Research has demonstrated how ejidos have selectively adopted some aspects of privatization, without undergoing the formal process of certifying and titling ejido lands [36,91,[93][94][95]. This research notes how ejidos internally and informally divided common forest areas, including permanent forest reserves established during the PPF, and converted them to individual landholdings.…”
Section: Policy and Institutional Constraintsmentioning
confidence: 99%
“…The reforms and resulting new Agrarian Law had two key impacts for forested ejidos in Quintana Roo, potentially constraining CFM's original promise of both environmentally and socially sustainable development. First, it promoted informal parcelization of forestlands-a process by which the ejido internally divides and distributes ejido lands without undergoing legal titling of individual properties [36,91,92]. While this process may have been occurring in ejidos of Quintana Roo before the 1992 reform, the new agrarian law, in some cases legitimized, and stimulated this informal parcelization.…”
Section: Policy and Institutional Constraintsmentioning
confidence: 99%
See 1 more Smart Citation